Factors Affecting Repayment Behaviour in Islamic Microfinance Programs - Abu Hassan, Mohamad Hanif; Yahya, Sofri; Shari, Wahidah (Human Resource Management Academic Research Society, 2023)
This study is primarily concerned with borrower behaviour in the context of microfinance financing repayment. The high non-performing loans (NPLs) incurred by microfinance institutions are one of the contributing factors to the failure to achieve the objective of poverty alleviation. This study used the quantitative approach, and structured questionnaires were distributed among respondents in Peninsular Malaysia who were selected via multistage random sampling. The results of the analysis showed that borrowers’ repayment behaviour was affected by their characteristics and accountability. Moreover, religiosity and business performance did not have a significant direct relationship with repayment behaviour. This research also found that accountability played a significant positive role as a mediator between borrower characteristics and repayment behaviour. This study makes a significant contribution to the knowledge of microfinance programmes, in which it explains repayment performance plays an important role in order to improve the social economy and alleviate poverty. The result also contributed to the practical aspect by suggesting ways to improve service and screening approaches to identify early warning signs and some factors that are potentially related to borrower behaviour